Enhanced bioactive properties of BiodentineTM modified with bioactive glass nanoparticles - Camila CORRAL NUÑEZ; Cristian COVARRUBIAS; Eduardo FERNANDEZ; Osmir Batista de OLIVEIRA JUNIOR
Abstract Objective To prepare nanocomposite cements based on the incorporation of bioactive glass nanoparticles (nBGs) into BiodentineTM (BD, Septodent, Saint-Maur-des-Fosses Cedex, France) and to assess their bioactive properties. Material and Methods nBGs were synthesised by the sol-gel method. BD nanocomposites (nBG/BD) were prepared with 1 and 2% nBGs by weight; unmodified BD and GC Fuji IX (GIC, GC Corporation, Tokyo, Japan) were used as references. The in vitro ability of the materials to induce apatite formation was assessed in SBF by X-ray diffraction (XRD), attenuated total reflectance with Fourier transform infrared spectroscopy (ATR-FTIR), and scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) analysis. BD and nBG/BD were also applied to dentine discs for seven days; the morphology and elemental composition of the dentine-cement interface were analysed using SEM-EDX. Results One and two percent nBG/BD composites accelerated apatite formation on the disc surface after short-term immersion in SBF. Apatite was detected on the nBG/BD nanocomposites after three days, compared with seven days for unmodified BD. No apatite formation was detected on the GIC surface. nBG/BD formed a wider interfacial area with dentine than BD, showing blockage of dentine tubules and Si incorporation, suggesting intratubular precipitation. Conclusions The incorporation of nBGs into BD improves its in vitro bioactivity, accelerating the formation of a crystalline apatite layer on its surface after immersion in SBF. Compared with unmodified BD, nBG/BD showed a wider interfacial area with greater Si incorporation and intratubular precipitation of deposits when immersed in SBF.